Disruptive selection and bet-hedging in planktonic Foraminifera: shell morphology as predictor of extinctions - Weinkauf, Manuel F. G.; Moller, Tobias; Koch, Mirjam C.; Kučera, Michal (Frontiers in Ecology and Evolution, 2014)
Extinction is a remarkably difficult phenomenon to study under natural conditions. This is because the outcome of stress exposure and associated fitness reduction is not known until the extinction occurs and it remains unclear whether there is any phenotypic reaction of the exposed population that can be used to predict its fate. Here we take advantage of the fossil record, where the ecological outcome of stress exposure is known. Specifically, we analyze shell morphology of planktonic Foraminifera in sediment samples from the Mediterranean, during an interval preceding local extinctions. In two species representing different plankton habitats, we observe shifts in trait state and decrease in variance in association with non-terminal stress, indicating stabilizing selection. At terminal stress levels, immediately before extinction, we observe increased growth asymmetry and trait variance, indicating disruptive selection and bet-hedging. The pre-extinction populations of both species show a combination of trait states and trait variance distinct from all populations exposed to non-terminal levels of stress. This finding indicates that the phenotypic history of a population may allow the detection of threshold levels of stress, likely to lead to extinction. It is thus an alternative to population dynamics in studying and monitoring natural population ecology.